STRATEGI PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) EKONOMI KREATIF KERAJINAN KULIT DI KABUPATEN MAGETAN (Studi Pada Dinas Perindustrian dan Perdagangan Kabupaten Magetan) - Putra, Langgeng R.; Mindarti, Lely Indah; Hidayati, Firda (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Micro, Small And Medium Enterprise Development Strategy of Creative Economy Leather In Magetan (Study At Magetan Industry And Trade Office). In the development of Micro, Small and Medium Enterprises leather crafts needed a good strategy to foster a more positive direction. The government, ie related agencies and related stakeholders are expected to provide solutions in every problem that exists. The purpose of this study is to describe, analyze and provide the right strategy formula to develop Micro, Small and Medium Enterprises leather crafts. The method chosen in this research is SWOT with score card. Field findings indicate that there are problems related to the development of production, human resource development and marketing.Â Keywords: Strategy, Development, UMKM, Leather Craft